Creating Place: The Role of Festival, Kajarī Folk Songs, and Rituals in Mirzapur - Chauhan M.; Mishra S. (My University, 2025)
This article examines the role of the Kajarī festival and folk songs in the socio-cultural lives of rural women in Mirzapur, Uttar Pradesh, India. It explores how the festival provides a unique space for rural women to assert their autonomy within a patriarchal society. Through ethnographic fieldwork, including the documentation of rituals, folk songs, and cultural activities, this study analyses the Kajarī festival as a place-making process. It argues that women use the performative space of Kajarī songs to express themselves and their experiences using strategies rooted in their traditions and rituals. The paper concludes that the Kajarī festival and its songs function as a critical outlet for emotional expression, social interaction, and self-expression, offering women a form of agency within their rural context. © (2024), (Universiti Pendidikan Sultan Idris). All rights reserved.